Pion, kaon, and (anti)proton production in U+U collisions at sNN =193 GeV measured with the STAR detector - STAR Collaboration (Physical Review C, 2023)
We present the first measurements of transverse momentum spectra of π±, K±, p(p¯) at midrapidity (|y|<0.1) in U+U collisions at sNN= 193 GeV with the STAR detector at the Relativistic Heavy Ion Collider (RHIC). The centrality dependence of particle yields, average transverse momenta, particle ratios and kinetic freeze-out parameters are discussed. The results are compared with the published results from Au+Au collisions at sNN= 200 GeV in STAR. The results are also compared to those from A Multi-Phase Transport (ampt) model. © 2023 American Physical Society.
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed